Evaluation of anteroposterior lip positions in the most-favored Iranian facial profiles using silhouette. - Ahmad Sodagar; Darab Gholami Borujeni (Tehran University of Medical Sciences, 2013)
One of the most important goals of orthodontic treatment is to create an esthetic, well balanced facial profile. However, the components of a well-balanced Iranian facial profile have not yet been established. The purpose of this study was to evaluate the anteroposterior lip position of the Iranian population and to compare the perception of orthodontists, dental students and orthodontic patients using a series of silhouettes with varying anteroposterior lip positions.Average female and male silhouette profiles were constructed from the profiles of 30 Iranian men and women with a normal skeletal relationship. The lips in each average profile were protruded or retruded in 2-mm increments and the 7 images were arranged randomly. Thirty orthodontists, 30 dental students and 30 orthodontic patients were asked to score each silhouette from 1 (very bad) to 5 (very good).Both the orthodontists and the students preferred the average profile for men and slightly more retruded lip position for women. Orthodontic patients had a wide range of preference for men and selected more retruded lip positions for women. The least-favored profile was the most protrusive in the 3 groups.These findings suggest that Iranian orthodontists, dental students and orthodontic patients prefer an average profile for men and slightly retruded profiles for women.